Blindfolding during wakefulness causes decrease in sleep slow wave activity. Issue 7 (13th April 2017) - Korf, Eva Magdalena; Mölle, Matthias; Born, Jan; Ngo, Hong‐Viet V.
Abstract: Slow wave activity (SWA, 0.5–4 Hz) represents the predominant EEG oscillatory activity during slow wave sleep (SWS). Its amplitude is considered in part a reflection of synaptic potentiation in cortical networks due to encoding of information during prior waking, with higher amplitude indicating stronger potentiation. Previous studies showed that increasing and diminishing specific motor behaviors produced corresponding changes in SWA in the respective motor cortical areas during subsequent SWS. Here, we tested whether this relationship can be generalized to the visual system, that is, whether diminishing encoding of visual information likewise leads to a localized decrease in SWA over the visual cortex. Experiments were performed in healthy men whose eyes on two different days were or were not covered for 10.5 h before bedtime. The subject's EEG was recorded during sleep and, after sleep, visual evoked potentials (VEPs) were recorded. SWA during nonrapid eye movement sleep (NonREM sleep) was lower after blindfolding than after eyes open ( P  < 0.01). The decrease in SWA that was most consistent during the first 20 min of NonREM sleep, did not remain restricted to visual cortex regions, with changes over frontal and parietal cortical regions being even more pronounced. In the morning after sleep, the N75‐P100 peak‐to‐peak‐amplitude of the VEP was significantly diminished in the blindfolded condition. Our findings confirm a link between reduced wake encoding and diminished SWA during ensuing NonREM sleep, although this link appears not to be restricted to sensory cortical areas. Abstract : Slow wave activity (SWA), that is, power in the 0.5–4 Hz EEG band during nonrapid eye movement (NonREM) sleep is considered in part a reflection of synaptic potentiation in cortical networks due to encoding of information during prior waking, with higher amplitude indicating stronger potentiation. Consistent with this concept, here we found that blindfolding human subjects during daytime wakefulness before nocturnal sleep produces a decrease in SWA during subsequent NonREM sleep, in comparison with sleep after an "eyes‐open" control condition. Notably, the decrease in SWA that was most consistent during the first 20 min of NonREM sleep, did not remain restricted to visual cortex regions, but was widely distributed with changes over frontal and parietal cortical regions being even more pronounced than over visual cortex.